In Vitro Activities and Inoculum Effects of Cefiderocol and Aztreonam-Avibactam against Metallo-β-Lactamase-Producing Enterobacteriaceae - Yu-Shan Huang; Pao-Yu Chen; Pei-Chun Chou; Jann-Tay Wang (Microbiology Spectrum, 2023)
ABSTRACT Cefiderocol and aztreonam-avibactam (ATM-AVI) both had activity against carbapenem-resistant Gram-negative bacilli, including those that produce metallo-β-lactamases (MBLs). We compared the in vitro activities and inoculum effects of these antibiotics against carbapenemase-producing Enterobacteriaceae (CPE), especially MBL-producing isolates. The MICs of cefiderocol and ATM-AVI were determined using broth microdilution method for a 2016 to 2021 collection of Enterobacteriaceae isolates which produced MBL, KPC, or OXA-48-like carbapenemases. MICs with high bacteria inoculum were also evaluated for susceptible isolates. A total of 195 CPE were tested, including 143 MBL- (74 NDM, 42 IMP, and 27 VIM), 38 KPC-, and 14 OXA-48-like-producing isolates. The susceptible rates of MBL-, KPC-, and OXA-48-like producers to cefiderocol were 86.0%, 92.1%, and 92.9%, respectively, and that to ATM-AVI were 95.8%, 100%, and 100%, respectively. NDM producers displayed lower susceptibility and higher MIC50s/MIC90s of cefiderocol (78.4%, 2/16 mg/L) than IMP (92.9%, 0.375/4 mg/L) and VIM (96.3%, 1/4 mg/L) producers. NDM- and VIM-producing Escherichia coli showed lower susceptibility to ATM-AVI (77.3% and 75.0%, respectively) compared to MBL-CPE of other species (100% susceptible). Inoculum effects for cefiderocol and ATM-AVI were observed among 95.9% and 95.2% of susceptible CPE, respectively. A switch from susceptible to resistant category was observed in 83.6% (143/171) of isolates for cefiderocol and 94.7% (179/189) for ATM-AVI. Our results revealed that NDM-producing Enterobacteriaceae had lower susceptibility to cefiderocol and ATM-AVI. Prominent inoculum effects on both antibiotics were observed for CPE, which suggested a risk of microbiological failure when they were used for CPE infections with high bacteria burden. IMPORTANCE The prevalence of infections caused by carbapenem-resistant Enterobacteriaceae is increasing worldwide. Currently, therapeutic options for metallo-β-lactamase (MBL)-producing Enterobacteriaceae remain limited. We demonstrated that clinical metallo-β-lactamase (MBL)-producing Enterobacteriaceae isolates were highly susceptible to cefiderocol (86.0%) and aztreonam-avibactam (ATM-AVI) (95.8%). However, inoculum effects on cefiderocol and ATM-AVI were observed for over 90% of susceptible carbapenemase-producing Enterobacteriaceae (CPE) isolates. Our findings highlight a potential risk of microbiological failure when using monotherapy with cefiderocol or ATM-AVI to treat severe CPE infection.